The Effect of E-Service Quality BYOND by BSI on Customer Satisfaction and Customer Loyalty at Bank Syariah Indonesia in Pekanbaru - Fitriana Tobing; Aida Nursanti; Henni Noviasari (Westscience Press, 2026)
This study aims to analyze the effect of E-Service Quality of BYOND by BSI on customer satisfaction and loyalty among customers of Bank Syariah Indonesia in Pekanbaru City. This research employs a quantitative approach, with the population consisting of all Bank Syariah Indonesia customers in Pekanbaru who use the BYOND by BSI application. The sampling technique used is purposive sampling, with a total sample of 130 respondents. Data analysis is conducted using the Structural Equation Modelling–Partial Least Square (SEM-PLS) method with the assistance of SmartPLS software version 4.1.1.8. The results indicate that E-Service Quality has a positive and significant effect on customer satisfaction. Customer satisfaction also has a positive and significant effect on customer loyalty. Furthermore, E-Service Quality has a positive and significant effect on customer loyalty through customer satisfaction as a mediating variable. These findings suggest that the better the quality of electronic services provided, the higher the level of customer satisfaction, which in turn encourages the development of customer loyalty.